Applicability of the Instrumented Pendulum Test for Assessing Limb Viscoelastic Properties in Neurological and Internal Diseases: A Narrative Review - Maria Stella Valle; Matteo Cioni; Cristina Russo; Lucia Malaguarnera; Antonino Casabona (Life)
Background: The pendulum test was first introduced by Wartenberg as a clinical tool for neurological examination in patients with hypertonia. It was later instrumented to measure the kinematic parameters of gravity-imposed knee movements in patients with spasticity. More recently, the instrumented pendulum test has enabled the quantification of stiffness, viscosity, and damping in both the lower and upper limbs across various neurological and internal diseases. Objective: To highlight the utility of the instrumented pendulum test as a valuable tool for the quantification of stiffness, viscosity, and damping of knee and elbow joints within a clinical setting. Design: Narrative review. Methods: A comprehensive search was conducted using PubMed/MEDLINE, focusing on the terms “pendulum test” combined with “viscosity”, “stiffness”, and “damping”. Results: The instrumented pendulum test effectively quantifies stiffness, viscosity, and damping of the knee and elbow across various conditions, including rheumatic diseases, chronic obstructive pulmonary disease, hypertonia, and hypotonia. Studies have also demonstrated correlations between these non-neural parameters and factors such as age and disease severity. Conclusions: Findings suggest that the instrumented pendulum test could serve as a valuable tool in clinical decision-making for targeted pharmacological treatments, such as botulinum toxin-A or hyaluronidase injections for spasticity, as well as interventions for myofascial system disorders.